Anaemia Spectrum within Chronic Liver Disease: A Descriptive Analysis - Reddy, N. Konda (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Chronic liver disease (CLD) is often associated with hematological abnormalities, affecting approximately 75% of patients. This condition may be exacerbated by deficiencies in folic acid and Vitamin B12, potentially due to inadequate dietary intake or malabsorption. Aim: This study aimed to evaluate the severity and type of anemia in CLD patients without overt bleeding for over 90 days, to improve management strategies and reduce related morbidity and mortality. Objective: Conducted at the Gastroenterology Department of Government General Hospital, Guntur Medical College, Andhra Pradesh, this year-long observational study took place from April 2022 to May 2023. We included 100 patients with CLD and anemia, all with hemoglobin levels above 10 g/ dL and no recent bleeding episodes. Result: It was observed that in ALC the most common anaemia is folic acid deficiency (39.7%) followed by Iron deficiency (37.2%), in HBV Iron deficiency (54.5%) followed by Folic acid deficiency (36.4%), in HCV both Iron and Folic acid deficiency were equally distributed (42.9%) and in NAFLD Iron and B12 deficiency were equally distributed (25%). Regarding severity, about 14% were severely anaemic flowed by 63% moderately anaemic and 23% were mild anaemic as noticed. Conclusion: The majority of patients are middle-aged (40–60 years), the family experiences severe psychological, social, and financial hardship.